A brief overview of Mozambique's rural development and the role of US assistance - Steven Kyle (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2003)
With an average per capita income of 154 in 2000 Mozambique is one of the poorest countries in the world but has also been one of the fastest growing economies through the 1990`s. Growth rates of 10% have been registered in some recent years though this has been offset to some extent by disastrous natural calamities including floods and droughts. The government remains committed to market reform and has at this point dismantled virtually all of the command and control apparatus that characterized the country through the mid-1990`s. Economic reform has been paralleled by political reform with the former armed opposition, RENAMO, now converted into a full participant in multiparty elections at all levels of government.
Keywords: 330; Ländliche Entwicklung; Entwicklungshilfe; Mosambik; USA